2010
DOI: 10.1017/s095026881000172x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and genetic relatedness ofListeriaspp. in two brands of locally processed ready-to-eat meats in Trinidad

Abstract: Contamination of locally produced, ready-to-eat meats by Listeria spp. has been previously reported at one processing plant in Trinidad. However, the status of this pathogen in locally produced products sold at retail outlets is unknown. This study was conducted to establish whether there is a risk to consumers of locally processed meats caused by the presence of Listeria spp., and whether a link exists between the presence of the pathogen in retail products and the manufacturing plant of one brand (B). Four h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…In this study, the prevalence of L. monocytogenes in RTE beef products (biltong, Vienna, "polony," etc.) was 10.7% which is much higher than the 4.4% reported for RTE meat products sampled in Mpumalanga province by Matle et al (2019), and the 8.1% documented in Trinidad and Tobago (Syne, Ramsubhag, & Adesiyun, 2011). The high prevalence of L. monocytogenes in RTE products in our study suggests that cross-contamination may have occurred during the handling and processing of the products.…”
Section: Discussioncontrasting
confidence: 66%
“…In this study, the prevalence of L. monocytogenes in RTE beef products (biltong, Vienna, "polony," etc.) was 10.7% which is much higher than the 4.4% reported for RTE meat products sampled in Mpumalanga province by Matle et al (2019), and the 8.1% documented in Trinidad and Tobago (Syne, Ramsubhag, & Adesiyun, 2011). The high prevalence of L. monocytogenes in RTE products in our study suggests that cross-contamination may have occurred during the handling and processing of the products.…”
Section: Discussioncontrasting
confidence: 66%
“…However, data from Trinidad showed that L. monocytogenes and other Listeria spp. were isolated from RTE, raw meat, food animals, and food processing environments, with at least one documented recall linked to contaminated RTE meat [ 39 , 40 , 41 , 42 ]. A recent outbreak involving contaminated ice cream made in the USA also prompted a recall that was extended to Caribbean countries [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies elsewhere have documented a lower prevalence of L. monocytogenes in RTE beef products, such as the reported 0.3% [ 65 ] and 3.7% to 5.1% in Ethiopia [ 66 ] than in our study. However, a higher prevalence of L. monocytogenes (44.3%) in RTE beef products was reported in Trinidad and Tobago [ 67 ]. The possibility of “polony” still serving as a vehicle and promoter of growth for L. monocytogenes in consumers cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%